ABIM 1971-2004 : Kepimpinan, Perjuangan Dan Pemikiran - Bahari, Mohd Azhar (2012)
ABIM is a dakwah movement that has significantly contributed to the rise of Islam in Malaysia. Since its establishment in 1972, ABIM has played a vital role in the struggle to restore the teaching of Quran and the Sunnah in the country. Its early history has proven that the movement has undergone various tribulations and challenges. From 1971 to 2004, ABIM had been led by five presidents who had managed to realise Islam as a complete way of life. ABIM leaders were ready to face imprisonment in their struggle to uphold the principles of justice and truth for the sake of Islam and for those being oppressed. ABIM has been functioning as a dakwah movement struggling for the truth and justice for almost 33 years. Both internal and external challenges as well as hindrances faced by ABIM are part of the process to develop and to upgrade the maturity level of the movement to achieve its objectives. In fact, the experience gained while facing the tribulations has led its leadership to make matured decisions for the benefit of the people. ABIM’s Non-Partisan approach on polital issues and its Manhaj Maliziy approach in dakwah has developed a high degree of confidence in the movement to execute its mission. Its struggle and thoughts for three decades have created a significant impact on the tranformation of the people in Malaysia. The movement’s involvement in the issues of injustice and oppression by the super powers against the Muslims has made it known as an Islamic movement that not only struggle for the locals but also for those being oppressed abroad. ABIM’s dakwah alliance and approaches have successfully generated new ideas in its effort to execute the idealism of Islamic struggle.